BRASIL DE FATO: TRAJETÓRIA, CONTRADIÇÕES E PERSPECTIVAS DE UM JORNAL POPULAR ALTERNATIVO - Moura, Ana Maria Straube de Assis (2009)
Investigation on the left-wing weekly newspaper Brasil de Fato, built by a group of leaders of social movements and representatives of civil society organizations, journalists, lawyers, artists, politically identified and joint to discuss a proposal submitted by the Landless Rural Workers Movement. Brasil de Fato was launched in January 2003 with the prospect of becoming a mass vehicle and completed six years of existence resisting adversities. The central objective is to analyze the process of construction and consolidation of this popular alternative newspaper since its design. Its trajectory is recovered in order to understanding not only the difficulties of maintaining a project with this profile, but also to analyze the internal and external contradictions that caused the changes in its original proposal. The methodology used for this purpose was bibliography research, semi-structured interviews with leaders and analysis of content. It was concluded that while the newspaper has faced a series of adverse conditions that justify the failure of its original proposal, but the characteristics of a social movement newspaper was already present in Brasil de Fato since its formation, especially regarding Landless Movement's conceptions for the newspaper.(AU)